2012
DOI: 10.1155/2012/201742
|View full text |Cite
|
Sign up to set email alerts
|

Omega-3 Status and the Relationship between Plasma Asymmetric Dimethylarginine and Risk of Myocardial Infarction in Patients with Suspected Coronary Artery Disease

Abstract: Background. Asymmetric dimethylarginine (ADMA) is an endogenous inhibitor of nitric oxide synthase. A previous rat study revealed an ADMA lowering effect following treatment with omega-3 polyunsaturated fatty acids (n-3 PUFAs). We sought to examine if an association between plasma ADMA and risk of acute myocardial infarction (AMI) was modified by serum n-3 PUFA status. Methods. The cohort included 1364 patients who underwent coronary angiography for suspected coronary artery disease in 2000-2001. Fatal and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
10
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 36 publications
4
10
2
Order By: Relevance
“…Nevertheless, they also observed no relationship between ADMA and the presence of 3-vessel CAD [14], in accordance with our data. Finally, as Schnabel et al [7] did not list any measure of angiographic CAD among covariates associated with ADMA in 1,874 CAD patients from the Athero Gene study, it can possibly be suspected that those correlations were statistically insignificant.…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, they also observed no relationship between ADMA and the presence of 3-vessel CAD [14], in accordance with our data. Finally, as Schnabel et al [7] did not list any measure of angiographic CAD among covariates associated with ADMA in 1,874 CAD patients from the Athero Gene study, it can possibly be suspected that those correlations were statistically insignificant.…”
Section: Discussionsupporting
confidence: 92%
“…(5) PRMT may be downregulated (reducing ADMA production) by reducing cholesterol concentration. (7) DDAH may be modified by reducing inhibitory influences (proton pump inhibitors,(37) smoking(5)), statins (38) or via upregulation by PPAR-γ (peroxisome proliferator-activated receptor γ) ligands (such as pioglitazone), (39) omega-3 fatty acids(40), and erythropoietin. (41) Interestingly, angiotensin-converting enzyme inhibitors may increase ADMA concentrations in hemodialysis patients via bradykinin signaling and may need discontinuation in select patients.…”
Section: Discussionmentioning
confidence: 99%
“…[12] With respect to SDMA, initial studies did not find an association with adverse outcomes,[7, 13, 14] but some more recent studies reported positive associations with all-cause mortality or CVD. [11, 15, 16] Overall, prior studies on ADMA/SDMA and CVD or all-cause mortality were derived from many different study populations (general population,[15, 17, 18] patients with CVD,[9, 11, 19, 20] renal diseases,[7, 13, 2124] diabetes,[25, 26] or critically ill patients from intensive care unit,[2729] respectively), differed in their methodological approaches (e.g. using types of samples (plasma vs. serum) or methods to determine the biomarker levels (HPLC vs. tandem mass spectroscopy vs. ELISA), or considered different confounders in their analysis.…”
Section: Introductionmentioning
confidence: 99%